2010
DOI: 10.1177/0960327110372402
|View full text |Cite
|
Sign up to set email alerts
|

Role of midkine in cadmium-induced liver, heart and kidney damage

Abstract: Accumulation of the widespread environmental toxin cadmium (Cd) in tissues results in toxicity. Cd, which can induce a broad spectrum of biological effects, is a toxic substance and is associated with inflammation and apoptosis. Midkine (MK) has fibrinolytic, antiapoptotic, transforming, angiogenetic and chemotactic activities. After Cd toxicity, we found increased MK expression in liver cells in an in vitro cell culture model. The aim of this study was to determine the possibility of relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…In the same study they showed that cytokine secretion was also lower in midkine deficient mice [8]. We previously reported that heart, liver and kidney tissue midkine levels increase in Cd toxicity [10]. This part of our study showed that Cd toxicity induces midkine secretion also in testis tissue.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In the same study they showed that cytokine secretion was also lower in midkine deficient mice [8]. We previously reported that heart, liver and kidney tissue midkine levels increase in Cd toxicity [10]. This part of our study showed that Cd toxicity induces midkine secretion also in testis tissue.…”
Section: Discussionsupporting
confidence: 78%
“…It was shown that midkine expression was upregulated in a marine gastropod limpet patella caerulea after they were exposed to sublethal doses of Cd [9]. We previously showed that midkine expression increases in different organ systems of the body in Cd toxicity [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, TNF-α is a common marker in the heart in response to stress such as cadmium. 47 An increase in TNF-α may play an important role in cadmium-induced DNA methylation as TNF-α may decrease the SERCA2a RNA and protein levels in the heart with an increased methylation in the SERCA2a promoter region, both of which were attenuated by 5-AZA. In addition, TNF-α may upregulate the expression of MeTase 1 in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] In addition, Cd-induced disruption of the blood-testis barrier, testicular damage, germ cell impairment, cardiomyopathy, renal failure, hypertension, arteriosclerotic heart disease 6 and immunosuppression in organs including the heart were reported in mice. 7,8 Furthermore, a signicant decrease of cell viability and Cd cytotoxicity to chicken hepatocytes were observed in the cells treated with Cd.…”
Section: Introductionmentioning
confidence: 99%